Effects of a Combination of Thyme and Oregano Essential Oils on TNBS-Induced Colitis in Mice - Alexandra Bukovská; Štefan Cikoš; Štefan Juhás; Gabriela Il’ková; Pavol Rehák; Juraj Koppel (Mediators of Inflammation)
We examined the anti-inflammatory effects of the combination of thyme and oregano essential oil dietary administered at three concentrations (0.4% thyme and 0.2% oregano oils; 0.2% thyme and 0.1% oregano oils; 0.1% thyme and 0.05% oregano oils) on mice with TNBS-induced colitis. Treatment of colitic animals with the essential oils decreased the mRNA levels of pro-inflammatory cytokines IL-1β, IL-6, GM-CSF, and TNFα, especially after application of the medium dose. The medium dose of the essential oils significantly lowered the amount of IL-1β and IL-6 proteins too. Moreover, administration of the medium dose decreased the mortality rate, accelerated the body weight gain recovery, and reduced the macroscopic damage of the colonic tissue. Our results indicate that combined treatment with appropriate concentrations of thyme and oregano essential oils can reduce the production of proinflammatory cytokines, and thereby attenuate TNBS-induced colitis in mice.